Slovanske knjige v XVI. stoletju - Zajc, Neža (Knjižnica, 2011)
Purpose: the article explores the Slavic typography in the Renaissance with special emphasis on the Cyrillic incunabula and on the complex process of building national languages in the Slavic regions, which are also related to the position of Christian theology (Orthodox, Catholic, and Protestant) of that time. Methodology/approach: the analysis of primary resources i.e. manuscripts and incunabula was used for the presentation of the complexity position of the Slavic languages in the 16th century. Results: it was difficult to separate the orthodox texts from the apocryphal contents of Christian texts. Research limitation: this study presents the general review and analysis of specific cases and as such it represents a basic introduction in to a more sophisticated research. Originality/practical implications:the study shows that the language disunity (the instability of the linguistic forms) could be one the reasons for difficultiesin printing the Slavic texts in 16th century.
Keywords: manuscripts; rokopisi; incunabula; inkunabule; printing; stari tiski; Slavic languages; slovanski jeziki; theological root of text; verska besedila; 16.st.; 16th cent.